2009
DOI: 10.1111/j.1559-1816.2009.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism and Cardiovascular Reactivity to Rejection Imagery1

Abstract: This study examined the interactive effects of imagined rejection and narcissism on cardiovascular reactivity (CVR). Participants completed measures of overt narcissism (Narcissistic Personality Inventory, NPI; Raskin & Hall, 1979), overt–covert narcissism (Margolis & Thomas, 1980), and trait self‐esteem. They then imagined 2 scenarios culminating in either interpersonal acceptance or rejection. Systolic (SBP) and diastolic blood pressure (DBP) and heart rate (HR) were assessed before, during, and after the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 101 publications
3
24
0
Order By: Relevance
“…Consistent with this assumption, rejection (and related social threats) are reliably associated with negative psychological consequences including negative mood (Blackhart, Nelson, Knowles, & Baumeister, 2009;Gerber & Wheeler, 2009) and impaired self-regulatory abilities (Baumeister, DeWall, Ciarocco, & Twenge, 2005). Studies have also revealed an association between rejection (and related social threats) and physiological responses including increased cardiovascular reactivity (Sommer et al, 2009;Stroud et al, 2000), increased levels of stress hormones (Blackhart et al, 2007;Dickerson, Mycek, & Zaldivar, 2008;Gunnar et al, 2003;Stroud et al, 2000Stroud et al, , 2002, and activation of components of the immune system related to inflammation (Dickerson et al, 2009;Slavich et al, 2010). These findings suggest that rejection Self-esteem, Daily rejection, and Health 17 elicits immediate physiological responses that may, over time, be detrimental to health and well-being.…”
Section: Responses To Rejectionmentioning
confidence: 83%
See 1 more Smart Citation
“…Consistent with this assumption, rejection (and related social threats) are reliably associated with negative psychological consequences including negative mood (Blackhart, Nelson, Knowles, & Baumeister, 2009;Gerber & Wheeler, 2009) and impaired self-regulatory abilities (Baumeister, DeWall, Ciarocco, & Twenge, 2005). Studies have also revealed an association between rejection (and related social threats) and physiological responses including increased cardiovascular reactivity (Sommer et al, 2009;Stroud et al, 2000), increased levels of stress hormones (Blackhart et al, 2007;Dickerson, Mycek, & Zaldivar, 2008;Gunnar et al, 2003;Stroud et al, 2000Stroud et al, , 2002, and activation of components of the immune system related to inflammation (Dickerson et al, 2009;Slavich et al, 2010). These findings suggest that rejection Self-esteem, Daily rejection, and Health 17 elicits immediate physiological responses that may, over time, be detrimental to health and well-being.…”
Section: Responses To Rejectionmentioning
confidence: 83%
“…There is growing evidence that individuals with negative self-views (such as those with low self-esteem) respond to rejection in ways that are harmful to their psychological well-being (e.g., Downey & Feldman, 1996;Ford & Collins, 2010;Murray, Bellavia, Rose, & Griffin, 2003;Nezlek, Kowalski, Leary, Blevins, & Holgate, 1997;Sommer & Baumeister, 2002). However, little work has been done to investigate whether they also respond to rejection in ways that are harmful to their physical well-being (Ford & Collins, 2010;Gunnar, Sebanc, Tout, Donzella, & Van Dulmen, 2003;Sommer, Kirkland, Newman, Estrella, & Andreassi, 2009). Additionally, the work that has been done has solely focused on immediate physiological responses to rejection.…”
mentioning
confidence: 93%
“…There is evidence that narcissism decreases with age into later adulthood (Foster et al, 2003); perhaps the physiological manifestations of narcissism change as well. Unfortunately, the vast majority of research on narcissism has focused on young adulthood, and the few studies linking narcissism with physiological processes have assessed only college-student participants (e.g., Sommer et al, 2009). Studying the physiological implications of narcissism beyond young adulthood is important because the adverse effects of narcissism may accumulate over time (Campbell & Campbell, 2009; Cramer & Jones, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study of men found that higher scores on the Narcissistic Personality Inventory (NPI), the most widely used measure of subclinical narcissism, predicted greater cardiovascular reactivity during anticipation of aversive stimuli (Kelsey, Ornduff, McCann, & Reiff, 2001). A more recent study examined changes in heart rate and blood pressure while participants imagined rejection or acceptance scenarios (Sommer, Kirkland, Newman, Estrella, & Andreassi, 2009). In this study, NPI scores predicted lower cardiovascular responses across tasks, whereas another measure of narcissism predicted greater cardiovascular reactivity only during the rejection scenarios.…”
Section: Narcissism Predicts Heightened Cortisol Reactivity To a Psycmentioning
confidence: 99%
“…Research applying more overt forms of exclusion through the use of direct inclusion/exclusion manipulations is limited, and has provided contradictory evidence regarding associated autonomic responses. Where overt exclusion scenarios have been applied in which participants have no prior expectations of inclusion or exclusion; increases in HR in response to exclusion have been reported (Sommer, Kirkland, Newman, Estrella & Andreassi, 2009). However, where participants have been invited to state prior expectations of their likely inclusion, a decrease in HR has been observed when those expectations were confounded by subsequent overt exclusion (Gunther-Moor, Crone & Molen, 2010).…”
Section: Belonging and Psychophysiological Responsesmentioning
confidence: 99%